Electoral dynamics in the states of India - Shastri, Sandeep; Kumar, Ashutosh, 1963-; Sisodia, Yatindra Singh (New York : Routledge, 2022)
"This volume presents a holistic picture of the electoral process in Indian states and the return of the BJP to power. Drawing on the 2019 elections, it presents ground-level data to understand various aspects of elections: the nature of campaigning, caste, class and identity politics, electoral issues, poll strategies of different parties in the fray, electoral issues, electoral verdicts, the contestants, the leadership factor, the formation of government, among other empirical details. The empirically rich essays underline the determinants of electoral behaviour by looking into the correlation between the background variables of voters and their voting choices. They also compare and contrast the 2019 election verdicts from the earlier elections held in the states under study. A long view of Indian state politics, this book will be essential reference for scholars and researchers of politics, especially political processes, elections, political participation, governance, and South Asian studies. It will also be of great interest to bureaucrats, think-tanks, and policymakers"--
Keywords: Elections -- India; Political participation -- India; Voting -- India; India -- Politics and government; POLITICAL SCIENCE / Political Process / Elections